Effect of pharmacological inhibition of Progesterone receptors PGRMC1 and nPR on bovine oocyte meiosis. (International Journal of Health, Animal Science and Food Safety, 2017)
Folliculogenesis is the fundamental process leading to oocyte maturation and its developmental competence, which are determined by oocyte and follicular cells interplay (Luciano et al., 2004).Recent studies in cattle describe Progesterone (P4) as a key molecule acting during follicle development through different signaling pathways involving different receptors (Aparicio et al., 2011, Nilsson et al., 2009). The aim of this study is to evaluate the effect on oocyte meiotic maturation of inhibiting two P4 receptors: Progesterone Receptor Membrane Component 1 (PGRMC1) and the classic nuclear Progesterone Receptor (nPR) respectively using the specific inhibitors AG205 and Aglepristone. Bovine cumulus cell-oocyte complexes (COCs) and denuded oocytes (DOs) were in vitro matured with different concentrations of AG205. Our results showed a decrease both in first polar body (PBI) extrusion and in the percentage of oocytes reaching MII stage in treated oocytes compared to controls (one way ANOVA, P
Keywords: Mammalian fertility; oocyte; Progesterone; PGRMC1; nPR.